2020
DOI: 10.3390/ijms21030709
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of the Cdc14 Phosphatase in Cell Cycle Control

Abstract: The Cdc14 phosphatase is a key regulator of mitosis in the budding yeast Saccharomyces cerevisiae. Cdc14 was initially described as playing an essential role in the control of cell cycle progression by promoting mitotic exit on the basis of its capacity to counteract the activity of the cyclin-dependent kinase Cdc28/Cdk1. A compiling body of evidence, however, has later demonstrated that this phosphatase plays other multiple roles in the regulation of mitosis at different cell cycle stages. Here, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 126 publications
(230 reference statements)
0
22
0
Order By: Relevance
“…Hutchinson-Gilford progeroid cell lines show bloated nucleoli (Buchwalter and Hetzer, 2017) and increased DNA damage that appears late in S phase (Chojnowski et al, 2020), echoing phenotypes observed in yeast strains with early replicating rDNA. Although the replication fork barrier protein Fob1p itself is not conserved in metazoans, some Cdc14p homologs are known to localize to the nucleolus (Berdougo et al, 2008;Kaiser et al, 2004;Manzano-López and Monje-Casas, 2020;Saito et al, 2004;Wu et al, 2008). Cdc14p regulation in metazoans may be more sensitive to early rDNA replication without the redundant Fob1p tether.…”
Section: Discussionmentioning
confidence: 99%
“…Hutchinson-Gilford progeroid cell lines show bloated nucleoli (Buchwalter and Hetzer, 2017) and increased DNA damage that appears late in S phase (Chojnowski et al, 2020), echoing phenotypes observed in yeast strains with early replicating rDNA. Although the replication fork barrier protein Fob1p itself is not conserved in metazoans, some Cdc14p homologs are known to localize to the nucleolus (Berdougo et al, 2008;Kaiser et al, 2004;Manzano-López and Monje-Casas, 2020;Saito et al, 2004;Wu et al, 2008). Cdc14p regulation in metazoans may be more sensitive to early rDNA replication without the redundant Fob1p tether.…”
Section: Discussionmentioning
confidence: 99%
“…The early anaphase release of Cdc14 has been linked to a variety of events necessary for the termination of mitosis (23,48) We found only one strong phenotype for the net1-6cdk allele in meiosis, a phenotype it shares with the classic FEAR mutants slk19Δ and spo12Δ -failure to disjoin the rDNA in meiosis I. From studies of mitotic cells we know that rDNA disjunction depends on two important activities of Cdc14 related to rDNA chromatin organization: condensin loading (17,20,49,50) and control of transcription within the rDNA (41,51).…”
Section: Discussionmentioning
confidence: 99%
“…The early anaphase release of Cdc14 has been linked to a variety of events necessary for the termination of mitosis (23,48) and meiosis I. However, it has been difficult to ascertain whether FEAR is directly responsible for the coincident events of chromosome segregation, spindle disassembly, spindle pole reduplication and CDK downregulation, particularly since the MEN becomes active soon after anaphase and is functionally redundant for the completion of those events.…”
Section: Discussionmentioning
confidence: 99%
“…This function of PP1 seems to be opposite to the mitotic exit promoting role of PP1 reported in animal cells. The fact that mitotic exit is achieved by the Cdc14 phosphatase in budding yeast, instead of the PP1 and PP2 phosphatases (Manzano-Lopez & Monje-Casas, 2020) is likely the reason for Glc7 gaining a different function after the anaphase onset during the narrow time window until exit from mitosis.…”
Section: Discussionmentioning
confidence: 99%